Beyond physical accessibility, bypassing health facilities offering caesarean section: insights from women in Dakar’s slums - Winfred Dotse-Gborgbortsi; Cheikh Faye; Arsene Brunelle Sandie; Fadima Yaya Bocoum; El Hadji Malick Sylla; Ndeye Awa Fall; Barrel Sow Gueye; Diarra Bousso Senghor; Birane Cissé; Ibrahima Ousmane Sy (BMJ Open)
Objective The study examines the geographic accessibility of Comprehensive Emergency Obstetric Care (CEmONC) among women residing in the slums of Dakar.Design The study is a cross-sectional geographic analysis of caesarean care utilisation in health facilities offering the service in Dakar.Setting The study was conducted in urban slum areas in Dakar.Participants 763 women living in urban slums who had undergone a caesarean section in six health facilities in Dakar between July and December 2022.Outcome measures The proportion of women bypassing the nearest health facility and travel time to health facilities.Results Key findings show that most women in Dakar’s urban slums live within 5 min from a health facility offering caesarean services, with an average travel time of 6.3 min. However, 44.3% bypassed nearby facilities, often travelling outside their district. Medical referral was the primary reason for bypassing (43.2%), followed by the search for higher quality care (13.5%) and reliance on family or social networks (14.9%). Only a small proportion (1.4%) cited more affordable treatment costs as a reason for bypassing.Conclusion Despite the good geographical accessibility of health facilities offering caesarean sections in Dakar, many women bypass nearby facilities due to medical referrals and the search for higher quality care, resulting in increased travel time and costs. Strengthening the quality and capacity of local health centres in urban slums is crucial to minimising unnecessary bypassing and ensuring timely access to essential obstetric services.